The role of the international Tour De Banyuwangi Ijen event in increasing the number of tourists for Banyuwangi Ijen crater destinations - Panji Sekar Pambudi; Mohammad Sabiq Irwan Hariandi (Jurnal Pariwisata Pesona, 2022)
The purpose of this study is to analyze the role of the International Tour de Banyuwangi Ijen (ITdBI) championship in increasing tourist visits to the Banyuwangi Ijen Crater destination. Respondents amounted to 100 tourists, including 80 domestic tourists and 20 foreign tourists. This study uses quota sampling. The data was processed using crosstabulation analysis and chi-square test, then continued with logistic regression. The research instrument is a questionnaire. The limitations of the research are the number of respondents and the willingness of respondents to fill out the questionnaire. The results showed that the role of sports championships analyzed on indicators of information, level of satisfaction, visiting enthusiasm, and recommendations contributed 75.9% to the increase in the number of tourists. Thus, the role of these major sporting events for tourists is as a medium of information, travel satisfaction, enthusiasm for repeated visits, and the willingness of tourists to recommend potential visitors. Future research is expected to include other factors involved in increasing tourist visits, especially tourists with sports motivation. The implementation of the next model and strategy is how to develop sustainable sports tourism in the Ijen crater tourist destination adapted to the concept of sustainable tourism development by considering environmental, socio-cultural and economic aspects.